Analisis Harga Pokok Produksi engan Pendekatan Full Costing untuk Penentuan Harga Jual pada Pabrik Tahu Pink Jaya - Hasmadana G.F. Kedah; Pius Bumi Kellen; Siprianus G. Tefa (Akuntansi, 2024)
This study aims to determine the cost of production calculated using the Full Costing method to determine the selling price. The approach in this study is a quantitative descriptive approach. This type of research is a case study research. The object of research is the Pink Jaya Tofu Factory located in Kupang City. Data collection methods in this study are observation, interviews and documentation. The data analysis technique used is quantitative descriptive with the Full costing approach. The calculation results show that the calculation of the cost of production using the Full costing approach gets higher results compared to the company's method. The difference in the cost of production is caused because the cost of production calculated by the company has not included all cost elements incurred in producing tofu such as factory overhead costs, depreciation costs and non-production costs while the Full Costing approach has charged all production costs, both fixed and variable, to the product, in addition to production costs, the Full costing method also charges non-production costs. As a result, there is a difference in the cost of production produced, from the difference in the cost of production the selling price produced is also different.